2002
DOI: 10.1053/jhep.2002.32101
|View full text |Cite
|
Sign up to set email alerts
|

Lower risk for alcohol-induced cirrhosis in wine drinkers

Abstract: Although there is a well-known relationship between total alcohol intake and future risk for cirrhosis, other factors such as the type of alcohol consumed are sparsely studied. The aim of this study was to assess the effects of wine compared with other types of alcoholic beverages on risk for alcohol-induced cirrhosis. In 3 prospective studies, 30,630 participants from the Copenhagen area were followed-up for a total observation time of 417,325 person-years. Information on weekly intake of beer, wine, and spir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
100
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(110 citation statements)
references
References 38 publications
6
100
3
1
Order By: Relevance
“…Cohort studies performed in the USA and Northern Europe all showed an increased risk of developing cirrhosis or HCC due to alcohol drinking, although some of them found a doseeffect relationship (Klatsky and Armstrong, 1992;Becker et al, 2002) whereas others found a threshold effect of 50-75 g/day, after which the risk does not increase further (Sorensen et al, 1998;Kamper-Jorgensen et al, 2004). Various factors may have caused these contrasting results, mainly confounding by other factors, inaccuracy in estimating the level of intake during follow-up, and the low power of the studies.…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 99%
“…Cohort studies performed in the USA and Northern Europe all showed an increased risk of developing cirrhosis or HCC due to alcohol drinking, although some of them found a doseeffect relationship (Klatsky and Armstrong, 1992;Becker et al, 2002) whereas others found a threshold effect of 50-75 g/day, after which the risk does not increase further (Sorensen et al, 1998;Kamper-Jorgensen et al, 2004). Various factors may have caused these contrasting results, mainly confounding by other factors, inaccuracy in estimating the level of intake during follow-up, and the low power of the studies.…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 99%
“…On the other side, unhealthy foods were considered for instance as soft drinks and saturated fatty acids, that is, dietary components well known to accelerate progression of liver disease [63,70] . Some studies have also suggested that a high percentage of red wine in the amount of alcohol consumed lowers the relative risk to develop (alcoholic) liver cirrhosis [71] . One explanation for this phenomenon may be resveratrol, a polyphenol in grapes, which is also found in red wines [72] .…”
Section: Confounding Dietary Factors Affecting Disease Progression Inmentioning
confidence: 99%
“…Alcoholic liver disease and its sequelae, ranging from alcoholic hepatitis to Laennec cirrhosis, are well described in the literature. The quantity and type of alcohol consumption that leads to hepatocellular injury are unknown, but studies have identified an association with spirits (distilled alcohol) rather than wine and beer [55][56][57]. Research has shown that Mexican American and black individuals are more prone to alcohol-induced hepatotoxicity than white individuals [58].…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%